Models of adjustment to illness - Afrasiabifar, A; Hasani, P; Fallahi Khoshkenab, M; Yaghamaei, F (Advances in Nursing & Midwifery, 2010)
Background and Aim Adjustment to illness is an important concept in nursing. Numerous studies have been conducted in this regards, however, available literature still shows controversy about the process of adaptation to illness and its criteria. This has resulted in different models for the process of adaptation to illness. This review article was intended to examine the concept of adjustment to illness, its different models and their strengths as well as weaknesses. Materials and methods For conducting this study, a comprehensive review of published literature in different Iranian and international databases including Iran Medex, PubMed, Elsevier, Scopus, Science Direct, ProQuest, and Ovid was carried out using keywords such as adjustment, adaptation, coping, and models of adjustment to illness. There was no time limitation for date of published literature. Findings Available studies and literature showed that there are three groups of biomedical, behavioral, and cognitive models are more applicable to nursing. Biomedical models consider such aspects of disease as its causes, symptoms and therapeutic interventions. Behavioral models describe patients' behavioral responses to illness. Cognitive models emphasize on cognitive appraisal of patients and their coping strategies. Conclusion Although these models provide valuable information about different aspects of adjustment to illness, they also have some limitations for clinical practice. By knowing them, nurses can plan, intervene and evaluate their care to facilitate adaptation to illness. Keywords: Adjustment, Adaptation, Adjustment to illness, Cognitive adjustment, Coping, Stress and coping model, Self-regulating model.